2021
DOI: 10.1136/bmj.n2321
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of non-steroidal anti-inflammatory drugs and opioid treatment for knee and hip osteoarthritis: network meta-analysis

Abstract: Objective To assess the effectiveness and safety of different preparations and doses of non-steroidal anti-inflammatory drugs (NSAIDs), opioids, and paracetamol for knee and hip osteoarthritis pain and physical function to enable effective and safe use of these drugs at their lowest possible dose. Design Systematic review and network meta-analysis of randomised trials. Data sources Cochrane Central Register … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
100
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(112 citation statements)
references
References 54 publications
4
100
0
8
Order By: Relevance
“…We summarised pain and function using SMDs, [23][24][25][26] and serious adverse events using relative risks. Summary estimates with 95% confidence intervals were obtained with the DerSimonian-Laird random effects model.…”
Section: Discussionmentioning
confidence: 99%
“…We summarised pain and function using SMDs, [23][24][25][26] and serious adverse events using relative risks. Summary estimates with 95% confidence intervals were obtained with the DerSimonian-Laird random effects model.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, treatment with proin ammatory factors, such as IL-1β or TNF-α, undermines cartilage ECM balance in chondrocytes and accelerates OA development in a mouse model [18]. Clinical application of anti-in ammatory drugs, such as etoricoxib, diclofenac, and celecoxib, only alleviates pain but cannot delay the progression of endogenous in ammation [19]. According to our ndings, the natural product ARB was a potential antiarthritic agent that inhibited the in ammatory cascade.…”
Section: Discussionmentioning
confidence: 98%
“…A recent network meta-analysis including 192 trials and > 100.000 patients recommended topical diclofenac to be the first pharmacological option due to its positive effect and safety profile. The authors of this network meta-analysis further concluded that the clinical benefit of opioids did not outweigh their potential harm [ 18 ].…”
Section: Discussionmentioning
confidence: 99%